The Impact of PowerPoint-Based Pedagogy on Student Achievement: Evidence from Indonesian Secondary Schools - Nur Baiti; Heny Friantary; Hengki Satrisno (Yayasan Darussalam Bengkulu, 2023)
This study aims to investigate the pedagogical impact of PowerPoint as an instructional medium on students’ achievement in Indonesian language learning, particularly in mastering personal and official letter writing. Adopting a quasi-experimental design with a pretest posttest control group, the research involved a population of 243 seventh-grade students at SMP Negeri 20 Bengkulu, from which 62 were purposively selected and assigned to experimental and control classes. Data were obtained through standardized achievement tests and analyzed using non-parametric statistics, including the Wilcoxon Signed Rank Test and the Mann-Whitney U Test, following normality and homogeneity assessments. The results demonstrate that students in the experimental class, who were instructed using PowerPoint, exhibited significantly higher learning gains than their counterparts in the control class (p < 0.05). These findings underscore the effectiveness of PowerPoint in fostering comprehension and performance in Indonesian language instruction, highlighting its potential as a practical and engaging medium to support innovative classroom practices.